Smart Irrigation System with Fuzzy Logic on Sunflower Plants Based on Internet of Things - Ulus Rahayu, Andri; Taufiqurrahman, Imam; Mutiarasari, Nurul Risti (Journal of Energy and Electrical Engineering, 2024)
Agriculture is a vital sector in the global economy, and to meet the growing demand, efficient management of water resources is a must. Amidst increasing climate instability, Internet of Things (IoT) technology has emerged as a potential solution. This research aims to develop an IoT-based smart irrigation system with fuzzy logic for sunflower plants. The system is designed to monitor and regulate water use automatically, increase productivity, and reduce waste of natural resources. This research uses an experimental model with the Mamdani method in fuzzy inference. It involves hardware (sensors), software (fuzzy logic), and IoT system. The results of this system implementation show that the system successfully performs watering management according to its environmental conditions.